Auditor Switching Among Malaysian Second Board Companies - Ismail, Shahnaz (2002)
The auditor switching phenomenon has been widely studied in the developed countries by academicians, accounting professionals and industry experts because of its implication to value credibility of financial reporting and the cost of monitoring management activities. Despite the growing concerns on this issue, few studies appear to have been made in Malaysia to examine the significant reasons and to estimate the shareholders' wealth effect. Thus the objectives of this study are (a) to identify the determinants of auditor switch among companies listed on Second Board of KLSE and (b) to examine the wealth effect of investors due to auditor switch. The period of study is from 1990 to 1999. During this period, there were about 297 companies listed on Second Board and 46 companies involved in auditor switch. This study uses two models namely, logistic regression model and event study method to examine the determinants of auditor switch and its wealth effect. The findings indicate that qualified audit report, audit fee, sale growth, return on asset and longevity of audit engagement, were the determinants of auditor switching. Using the event study method, the findings on the investors reaction surrounding the announcement date indicate that investors on average reacted positively to auditor switch in general with a significant positive excess return at switched date. The findings also indicate that investors reacted positively towards switching from Tier2 to Tier! and negatively towards switching involving Tierl to Tier2 auditor. Further results show that during the financial crisis of 1997, switching (either to Tierl or Tier2) has no significant impact on shareholder's wealth.